Depletion of Amoxicillin Residue in Edible Tissue of Broiler Chicken by Different Cooking Methods - Aynalem Lakew; Negussie Megersa; Bhagwan S. Chandravanshi (International Journal of Analytical Chemistry)
A new simple isocratic, RP-HPLC method, was developed and validated to estimate amoxicillin (Amox) residue depletion caused by different cooking methods in broiler chicken tissue. The limit of detection (LOD) and the limit of quantitation (LOQ) were 1.32 and 4.00 µg mL−1, respectively. The calibration plot was linear over the concentration range of 0.05–250 µg mL−1, and the relative standard deviation (RSD) values were less than 8%. The effects of various cooking methods (boiling, pan-frying, and microwaving) on residues of Amox were conducted under different combinations of temperature and time. Moreover, the heat stability of Amox standard solutions under boiling water and cooking oil at 100°C was investigated. Amox remained stable for 5–15 min in boiling water, the concentration was significantly reduced in the range of 70–87%, and additional new peaks of the degraded compounds appeared at 30–45 min. In pan-frying, the residue remained stable for 15 min at 100°C and then depleted to 81–92% after 30–45 min. Due to dehydration, the residue concentration showed an increment from 101 to 112% at 150°C. The total decomposition of Amox was observed at 200°C, 30–45 min due to high temperature and long-time effects. In microwave cooking using 500 W, 0.5–2 min, the depletion was insignificant. This study shows that sufficient cooking temperature and time can have a significant effect on the depletion of Amox residues.